Stability and Optimal Control of an Mathematical Model of Tuberculosis/AIDS Co-infection with Vaccination - Leontine Nkague Nkamba; Thomas Timothee Manga (New Ideas Concerning Science and Technology Vol. 11, 2021)
This paper focuses on the study and control of a non linear mathematical epidemic model (S Svih V E LI ) based on a system of ordinary differential equation modeling the spread of tuberculosis infectious with VIH/AIDS coinfection. Existence of both disease free equilibrium and endemic equilibrium are discussed. Reproduction number R0 is determined. Using Lyapunov-Lasalle methods, we analyze the stability of epidemic system around the equilibriums (Disease free and endemic equilibrium). The global asymptotic stability of the disease free equilibrium whenever Rvac < 1 is proved, where R0 is the reproduction number. We prove also that when R0 is less then one, Tuberculosis can be eradicated. Numerical simulations, are conducted to approve analytic results. To achieve control of the disease, seeking to reduce the infectious group by the minimum vaccine coverage we can have. a control problem is formulated. The Pontryagin’s maximum principle is used to characterize the optimal control. The optimality system is derived and solved numerically using the Runge Kutta fourth procedure.